The IceCube Neutrino Observatory - Contributions to ICRC 2017 Part I: Searches for the Sources of Astrophysical Neutrinos - Aartsen, MG; Ackermann, M; Adams, J; Sarkar, S; IceCube Collaboration (International School for Advanced Studies, 2017)
Papers on the searches for the sources of astrophysical neutrinos, submitted to the 35th International Cosmic Ray Conference (ICRC 2017, Busan, South Korea) by the IceCube Collaboration Contents 1 - Searching for VHE gamma-ray emission associated with IceCube astrophysical neutrinos using FACT, H.E.S.S., MAGIC, and VERITAS 2 - Search for point-like sources in the astrophysical muon neutrino flux with IceCube 3 - Search for weak neutrino point sources using angular auto-correlation analyses in IceCube 4 - All-sky search for correlations in the arrival directions of astrophysical neutrino candidates and ultrahigh-energy cosmic rays 5 - Results of IceCube searches for neutrinos from blazars using seven years of through-going muon data 6 - IceCube Search for Neutrinos from 1ES 1959+650: Completing the Picture 7 - Using all-flavor and all-sky event selections by IceCube to search for neutrino emission from the Galactic plane 8 - Constraints on diffuse neutrino emission from the Galactic Plane with 7 years of IceCube data 9 - Search for extended sources of neutrino emission with 7 years of IceCube data 10 - Search for a cumulative neutrino signal from blazar flares using IceCube data 11 - Investigation of Obscured Flat Spectrum Radio AGN with the IceCube Neutrino Observatory 12 - Realtime neutrino alerts and follow-up in IceCube 13 - Search for High-Energy Neutrino Emission from Fast Radio Bursts 14 - IceCube as a Neutrino Follow-up Observatory for Astronomical Transients